Reliability-based dynamic multicast group formation provisioning local adjustment ensuring quality of service globally in MANETs. Issue 2 (4th March 2021) - Tyagi, Shobha; Som, Subhranil; Khatri, S. K.
Abstract : Mobile Ad hoc Networks (MANETs) is an infrastructure less and random mobility-based class of wireless networks with seamless possibilities of 'on the fly' communication through self-coordination among autonomous mobile nodes while being in the transmission range of each other. This low cost, easy to deploy, simplicity, and self-organisation of MANET altogether revolutionised wired networks and could connect otherwise unreachable terrains/sites. To handle the severity of colossal issues like dynamic topology, scarce resources and frequent rupturing of established routes in MANETs, conservation of energy becomes inevitable to administer contemporary applications. After an extensive literature survey for provisioning reliability and multicast routing in MANETs, researchers concluded the conservation of mobile nodes energy embrace a very consequential role in extending network life. The PLA (Proposed Local Adjustment) model is based on eliminating flooding, preserving nodes battery life by selectively choosing forwarder node at each hop level, and handling route failures locally, eventually makes the network more robust and resilient. The PLA model when simulated on NS2.35 against AODV on various parameters like control overhead generated, packet delivery ratio, energy conserved index, produced quite convincing and promising results, to be offered to remote and rescue-based applications in the vicinity of infrastructure less regions.